Therapeutic use of psilocybin: Practical considerations for dosing and administration - MacCallum, Caroline A.; Lo, Lindsay A.; Pistawka, Carly A.; Deol, Jagpaul Kaur (Frontiers in Psychiatry, 2022)
The interest in psilocybin as a therapeutic approach has grown exponentially in recent years. Despite increasing access, there remains a lack of practical guidance on the topic for health care professionals. This is particularly concerning given the medical complexity and vulnerable nature of patients for whom psilocybin-assisted psychotherapy may be considered. This article aims to provide health care professionals with an overview of practical considerations for psilocybin therapy, rooted in a patient safety focus. Within this piece we will review basic psilocybin pharmacology and pharmacokinetics, indications, practical therapeutic strategies (e.g., dosing, administration, monitoring) and safety considerations (e.g., contraindications, adverse events, and drug interactions). With this information, our goal is to increase the knowledge and comfort of health care professionals to discuss and counsel their patients on psilocybin therapy, ultimately improving patient care and safety.